p-ADIC HODGE THEORY FOR RIGID-ANALYTIC VARIETIES – CORRIGENDUM. (12th August 2016) - SCHOLZE, PETER
Abstract : The author would like to make some changes to the previously published article [1 ] by correcting two definitions.